Stability of Tissue Augmented with Deproteinized Bovine Bone Mineral Particles Associated with Implant Placement in Anterior Maxilla - David Buntoro Kamadjaja; Ni Putu Mira Sumarta; Andra Rizqiawan (Hindawi Limited, 2019)
Background. Implant placement in defective anterior maxilla poses a great challenge regarding functional and aesthetic outcomes. Therefore, it requires predictable alveolar ridge augmentation. Deproteinized bovine bone mineral (DBBM) particle has commonly been used for bone grafting. However, it is associated with low resorption rates which potentially compromise the outcome of horizontal augmentation in conjunction with implant placement. Aims. This study is aimed at evaluating the stability of tissue augmented with DBBM particle associated with implant placement in the anterior maxilla. Materials and Methods. The inclusive criteria consist of patients being treated with guided bone regeneration (GBR) incorporating the use of DBBM particles with either a simultaneous or staged approach. The parameters analyzed include the implant survival rate, post-GBR clinical stability based on tissue resorption level, and the tissue stability between simultaneous and staged approaches. Statistical analysis using Mann-Whitney test is performed with significance determined at p value < 0.05. Results. Seventeen patients with 23 implant placements satisfy the criteria for this study. Simultaneous approach is adopted in 18 (78.3%) implants and a staged approach in 5 (21.7%) implants. The implant survival rate is 100%. The evaluation of horizontal tissue stability reveals a low resorption level in 19 (82.6%) implants, while moderate and high resorption levels are found in 3 (13.0%) and 1 (4.3%) implants, respectively. The statistical analysis shows that the simultaneous approach produces significantly (p=0.005) lower resorption level compared to the staged approach. Conclusion. Horizontal ridge augmentation using DBBM particles associated with implant placement in the anterior maxilla produces good clinical stability. The stability appears to be higher in the simultaneous approach compared to the staged approach.